Early childhood caries sequelae and relapse rates in an Australian public dental hospital. Issue 1 (20th May 2022) - Tsai, Carrie; Li, Ang; Brown, Sophie; Deveridge, Caitlin; El Gana, Rania; Kucera, Alice; Irving, Michelle; Kumar, Harleen
Abstract: Background: Early childhood caries (ECC) remains one of the most prevalent childhood diseases in Australia, disproportionately affecting disadvantaged populations. Aim: To investigate the ECC experience including risk factors, incidence of caries, pain and infection as well as relapse rates of caries and secondary dental general anaesthesia (GA). Design: A retrospective cohort study included dental records of children with ECC, aged <72 months at an Australian public dental hospital paediatric dentistry department from 2013 to 2015 ( n = 102). Dental caries, pain, infection, referral patterns, demographic and caries risk factor data were recorded for 24 months. Descriptive statistics were used for patient characteristics and clinical data, and Kaplan–Meier curves and parametric exponential survival models for time‐to‐event series. Results: The study population demonstrated higher‐than‐national average dmft and disease progression at baseline. Major risk factors for the development of caries, pain and infection were daily consumption of sweetened beverages, poor oral hygiene, residing in lower socio‐economic areas, older age and being male. Rates of caries relapse and new referral for secondary treatment under general anaesthesia were relatively high. Conclusion: A high degree of ECC progression and recurrence in this population indicates a need for a more comprehensive approach to ECC addressing multilevel root causes and systemic risk factors.